Stress response of the coral Stylophora pistillata towards possible anthropogenic impacts in the Gulf of Aqaba, Red Sea - Fuad Al-Horani; Sewar T. Al-Talafhah; Maysoon kteifan; Emad I. Hussein (Kuwait Journal of Science)
Coral deterioration is often linked with coastal pollution. This study aims to study the biochemical stress responses in the coral Stylophora pistillata collected and/or planted in impacted and non-impacted coastal sites in the Gulf of Aqaba-Red Sea. DNA damage and lipid peroxidation were analyzed to measure stress in corals. High DNA damage was found in corals from the polluted sites, while lipid peroxidation in field samples was not consistent in long term incubation periods. The incubation of corals with copper and lead produced high levels of DNA damage and lipid peroxidation compared with control samples. The results suggested that corals suffer at the subcellular level, though they look healthy. The consequences of such stress might affect the fecundity and growth rates of the corals. The results suggest that the biomarkers used are efficient tools for early stress detection in corals, though the cost of DNA damage is relatively expensive compared with the lipid peroxidation test.